Pemberian Ganti Rugi Terhadap Pengadaan Tanah Oleh Pemerintah Untuk Kepentingan Umum - Luh Nyoman Diah Sri Prabandari; I Wayan Arthanaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
Land purchasing is an activity taken by government in order to build public fasilities, purchasing also done by giving some compesation to society that affected. During purchasing activity never runs smooth , where mostly some people who gets land purchase is not santisfied with the amount of compensation that given by government. Regarding those matters, we may conclude there are 2 problems those are : 1. What Is the juridical basis for land acquistion in the public interest?, 2. How is the mechanism of compesation in land purchasing for public that held by goverment ?. Research that an be used to solve the problem is normatif research method by studying the valid rules. Juridis platform land purchasing is President policy no 71 year 2012 about land enforcement to public needs, the regulation no 2 year 2012 about land purchasing for public developing. Compensation mechanism on land purchasing must be based on the forum between committee and the right holder of the land or plants that’s exist on it, that during the interpretation or the quotation the amount of compensation should be agreed and must be based on the local public price.